Analisis Furosemid Injeksi 10 mg/mL Dalam Validasi Proses Furosemid Injeksi 10 mg/mL Secara Spektofotometri UV-Vis - Trisna, Meyci; Mujiyanti, Apri; Azharman, Zefri; Antara, Nico (Akta Kimia Indonesia, 2024)
Furosemide is a diuretic derivative of anthranilic acid. The diuretic activity of furosemide is mainly by inhibiting the absorption of sodium and chloride. This study aims to validate the production process of 10mg/mL injection furosemide; therefore, it can be known whether the production process has run well and product is suitable for consumption. There are eight parameters in this study including the determination of furosemide concentration in the sample, the results obtained that the concentration is 102.14% which is a qualified number. Furthermore, the analysis of the uniformity of the final mass concentration, with the difference in concentrations obtained meets the requirements, the RSD value is 1.64. This indicates that the mixing process has run well, accordingly it is able to produce a homogeneous product. Furthermore, the determination of volume uniformity, sterility, endotoxins, bioburden, pH and particulates also provides qualified results, hence the production process of the three batches analyzed runs well so as to produce qualified and consistent products.